Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1121/1.4807510
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory overlap as a function of voicing in French and German consonant clusters

Abstract: The effects of laryngeal specification on the timing of supra-laryngeal articulations have so far received little attention. Previous research has shown that German-but not French-mixed-voicing clusters are produced with less articulatory overlap than phonologically fully voiced clusters. Articulatory and acoustic data of labial and velar stops as simple onsets and in stop + /l/ clusters are examined to probe the causes for this cross-linguistic difference in the light of the different voicing implementations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The fairly large range of variation for VOT in the French data of Figure 4 indicates that, currently, the language has a fair amount of latitude in timing of voice onset. This may also explain why the French VOT values found here are higher than those found, for example, in our own previous work (Bombien & Hoole, 2013). Because of the constraints of the transillumination technique, all of the target consonants were followed by a high vowel (whereas in our earlier experiment, which used electromagnetic articulography, we used predominantly low vowels).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The fairly large range of variation for VOT in the French data of Figure 4 indicates that, currently, the language has a fair amount of latitude in timing of voice onset. This may also explain why the French VOT values found here are higher than those found, for example, in our own previous work (Bombien & Hoole, 2013). Because of the constraints of the transillumination technique, all of the target consonants were followed by a high vowel (whereas in our earlier experiment, which used electromagnetic articulography, we used predominantly low vowels).…”
Section: Discussioncontrasting
confidence: 50%
“…For any given item, consider the effect of varying the position of the right edge of the P bar while keeping the total length of the ABD and ADD bars constant. For more background for such a scenario, see, e.g., Bombien & Hoole, 2013;Hutters, 1985.) The pattern for relative timing of peak glottal opening shown in Figure 5 follows the VOT pattern very closely, which is not surprising because the timing of peak glottal opening is the interarticulatory coordination relation most directly responsible for VOT at the acoustic surface.…”
Section: Discussionmentioning
confidence: 70%
“…This finding is in line with an earlier one by Pouplier (2012), which reports about the same lag duration for /bl/ as for /pl/ (her Figure 3). As an explanation for this finding, Bombien and Hoole (2013) discuss different oral-laryngeal coupling relations. Whereas in German clusters, all oral gestures are assumed to be coupled to one laryngeal gesture, in French, each oral gesture has its own coordination with a glottal gesture.…”
Section: Consonant-consonant Coarticulationmentioning
confidence: 85%
“…1 As a result of that, the prevocalic consonant is delayed. This hypothesis was tested by Bombien and Hoole (2013). They compared lag durations in German and French /kl, gl, pl/ and /bl/.…”
Section: Consonant-consonant Coarticulationmentioning
confidence: 99%
“…Overlap between consonants is both language-specific [16] [17] and determined by a variety of factors [17] [19]. Order of place of articulation affects degree of overlap; research on Georgian [4], French [20] and Korean [21] has shown that back-to-front clusters are less overlapped than front-to-back clusters.…”
Section: Overlapmentioning
confidence: 99%